Comparison of perioperative parameters in one-handed rotational phacoemulsification versus conventional phacoemulsification and femtosecond laser-assisted cataract surgery - Samuele Gigliola (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To compare perioperative parameters of one-handed rotational phacoemulsification technique (one-handed phaco-roll) with each of other two techniques, “Divide et Conquer” and femtosecond laser-assisted cataract surgery (FLACS) METHODS: In this retrospective and comparative cohort study, eyes with uncomplicated cataract (nuclear density grade 2 to 3) treated routinely with one-handed phaco-roll (n=23; Group 1) or “Divide et Conquer” (n=23; Group 2) or FLACS (n=23; Group 3) were enrolled. Intraoperative parameters including effective phaco-time (EPt), ultrasound time (USt), aspiration time, surgical time, phacoemulsification (phaco)-power, balanced salt solution (BSS) use, cumulative dissipated energy (CDE) were recorded and compared. Clinical outcomes including best corrected visual acuity (BCVA), corneal endothelial cell density (ECD), endothelial cell loss (ECL), central corneal thickness (CCT) and central macular thickness (CMT), were assessed and compared pre-operatively and at 1mo after surgery. RESULTS: Aspiration and surgical time, and BSS used were lower in Group 1 (P<0.01) than other groups. EPt, phaco-power and CDE were lower in Group 1 (P<0.05) than Group 2 but not significantly different from Group 3. In Group 1, USt was lower (P<0.05) than Group 2 but higher (P<0.05) than Group 3. BCVA improved in all groups without significant difference between Group 1 and the other ones. No significant differences regarding all post-operative morphologic outcomes (ECD, ECL, CCT, CMT) were reported. No clinical complications occurred. CONCLUSION: One-handed phaco-roll seems to be less time-consuming than “Divide et Conquer” and FLACS and less energy-consuming than “Divide et Conquer”. Furthermore, one-handed phaco-roll seems to have an equal safety profile compared to the other two techniques.